The Strategic Planning of Cyber Public Relations at Faith-Based Organization - Putri, Tafsiroh Tenggara; Damayanti, Syafira; Fauziah, Kholifatul (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This paper examines the critical interpretation of strategic planning of cyber public relations in a faith-based organization. Specifically, this paper aims to elaborate on how the administrators of the Central Board of Muhammadiyah conduct their relationship with the public through their official social media, Lensamu, which consists of Instagram, Facebook, YouTube, and Twitter accounts. This study uses the descriptive qualitative analysis method with Lutrell's theory as the framework of analysis. Data collection was operationalized through interview, observation, and documentation. Lutrell's strategic planning of social media consists of sharing, optimizing, managing, and engaging. The result shows that all steps of strategic planning were carried out by Lensamu. Sharing and optimizing are optimally executed. Meanwhile, managing and engaging still need to be developed. Theoretically, this study contributes to a cyber public relations scheme of faith-based organizations. Besides, this study provides a significant lesson learned for social media administrators, especially those working in the faith-based area.